Blow-Up for a Stochastic Viscoelastic Lamé Equation with Logarithmic Nonlinearity. (19th April 2021) - Benramdane, Amina; Mezouar, Nadia; Alqawba, Mohammed Sulaiman; Boulaaras, Salah Mahmoud; Cherif, Bahri Belkacem
Abstract : In this paper, we consider an initial boundary value problem of stochastic viscoelastic wave equation with nonlinear damping and logarithmic nonlinear source terms. We proved a blow-up result for the solution with decreasing kernel.